Embodied inter-referencing: encounters with and among "Asian" students in the Australian classroom. Issue 2 (3rd April 2019) - Park, Jane Chi Hyun
ABSTRACT: This essay examines the pedagogical practice of referencing my experiences as a transnational Korean American woman in the classroom and considers how it opens up space for domestic and international students of East, Southeast, and South Asian backgrounds to reflect on their different identities, histories, and cultures. In particular, it focuses on how this practice enables Asian students to share their experiences of and insights about racial difference, racism, and whiteness in Australia and other parts of the world. Building on the concept of Asian "inter-referencing" from Chua Beng Huat (2015), I coin the term "embodied inter-referencing" to describe the strategic ways I use autobiographical narrative to create an inclusive, interactive, and mutually respectful learning space. I centre here on how some Asian students respond to this strategy by telling their own stories and in the process, create transnational, diasporic, and inter-Asian affective communities inside and outside the classroom.